2018
DOI: 10.1111/jrh.12302
|View full text |Cite
|
Sign up to set email alerts
|

Rural Health Networks: How Network Analysis Can Inform Patient Care and Organizational Collaboration in a Rural Breast Cancer Screening Network

Abstract: This study found that geographic location of resources is an important factor in rural health care providers' referral decisions and demonstrated the usefulness of network analysis for understanding rural health networks. These results can be used to guide delivery of patient care and strengthen the network by building resources that take location into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…These included size, number of connections, cohesion (level of participation, density, and centralization), function (information sharing or referrals), and integration. 16,17,22,58-90 Eight studies identified organizations central to the network and/or network brokers (organizations serving as a bridge between other organizations) and characterized how those organizations positively contribute to network development. Another 5 studies identified and characterized sub-networks which included smaller groups of organizations within the overall network.…”
Section: Resultsmentioning
confidence: 99%
“…These included size, number of connections, cohesion (level of participation, density, and centralization), function (information sharing or referrals), and integration. 16,17,22,58-90 Eight studies identified organizations central to the network and/or network brokers (organizations serving as a bridge between other organizations) and characterized how those organizations positively contribute to network development. Another 5 studies identified and characterized sub-networks which included smaller groups of organizations within the overall network.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, communication among people and organizations during program implementation was always described positively in these studies (see networks and communications construct under Inner Setting domain), with little discussion of challenges and potential solutions. Approaches such as network analysis could provide more insight into the density and functionality of networks of healthcare and community-based organizations, particularly in rural areas where opportunities for collaboration may be constrained by geography [ 49 , 50 ]. In addition, some authors have called for greater attention to communication theory in implementation science research [ 51 , 52 ]; these paradigms could provide insight into how network nodes co-create priorities, information, and resources related to public health and cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Th e urban environment was the source of residence for 100% of the patients included in the study, the access to specialized medical services being limited for patients located in rural areas 9 .…”
Section: Demographic Datamentioning
confidence: 99%